Customer Relationship Management Pada Aplikasi Pengelolaan Pemesanan Makanan Nasi Bakar Lovely Berbasis Web dan Mobile - Christian Yacobus; Bagus Mulyawan (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
The Sole proprietorship of Nasi Bakar Lovely is a Sole proprietorship which is engaged in culinary with its main menu is Nasi Bakar with various kinds of contents. The problem is lack of media to reach customers who do not know the existence of this Nasi Bakar Lovely , this causes the Nasi Bakar Lovely just make Nasi Bakar if there are customers who order it, this thing makes Nasi Bakar lose competitiveness with other businesses and can go out of business. This paper offers a solution to solve the problem by designing a web-based application using C# and android programming language where the process of making this application is made by using model waterfall as the model. With the existence of such a solution is expected the owner of Nasi Bakar Lovely still can compete and not fold.